PENGARUH EDUKASI REBUSAN AIR DAUN SALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DENGAN PENYAKIT JANTUNG - Sundari, Indah; Apidianti, Sari Pratiwi (LPPM Institut Pendidikan Nusantara Global, 2025)
Elderly is a condition where individuals have a high risk of developing degenerative diseases such as Coronary Heart Disease (CHD), hypertension, diabetes mellitus, rheumatism, and cancer. However, the most common disease in the elderly is hypertension. Hypertension can be caused by various risk factors that vary such as family history, increasing age in different genders. Men tend to have higher blood pressure at a young age than women. High blood pressure can be overcome with non-pharmacological management, one of which is with boiled bay leaves. Bay leaves contain flavonoid compounds, where flavonoids containing quarcertin have an effect as a vasodilator, antiplatelet, and antiproliferative and lower blood pressure, the result of oxidation and repair of body organs that have been damaged by hypertension. Objective: To provide knowledge and understanding to the community about hypertension therapy using boiled bay leaves. Method: Community service activities were carried out in Padelegan Village, Pademawu District, Pamekasan Regency on September 24, 2025. The number of participants was 20 elderly people. Blood pressure measurement using a tensiometer measuring instrument with grouping where normal conditions are if SBP≤120/80 mmHg, normal-high=130-139/85-89 mmHg, grade 1 hypertension=140-159/90-99 mmHg, grade 2 hypertension=160-179/100-109 mmHg and hypertension grade SBP≥180/110 mmHg. Therapeutic action by drinking boiled bay leaves water ±60 ml with a frequency of 2x a day before each meal for 1 week. Results: Obtaining data on blood pressure measurements of respondents before therapy with boiled bay leaves, most of them were in normal-high conditions, namely 13 (65.0%), while after therapy most were in normal conditions, namely 7 (35.0%). Conclusion: Bay leaf decoction therapy has an effect in lowering blood pressure in elderly with hypertension. Increasing knowledge of non-pharmacological therapy has an impact on the confidence of the elderly in controlling their blood pressure. Suggestion: The community can apply knowledge of bay leaf decoction therapy independently as a control for elderly people with hypertension and share knowledge with families, the environment and other areas where the incidence of hypertension is still high but have not yet received knowledge of bay leaf therapy.